The external aerodynamics of the ahmed body reference geometry: a numerical analysis using cfd (2020)
In the present study, numerical CFD simulations were developed on the Ahmed body reference geometry in order to understand and analyze its external aerodynamics, such as: generation of vortices; fields of velocity around the geometry, mainly in the wake part; generation of drag by pressure and drag by friction; and sustentation generation. On the other hand, in the validation process of results, fundamental parameters were considered, such as: mesh independence study, computational domain independence study and mesh quality analysis. In addition, different turbulence models were used to determine which best predicted the airflow around the geometry. The results obtained through the numerical simulations were verified exhaustively to guarantee the veracity of the simulations, additionally a comparison was made with experimental investigations, showing high concordance between the results.